PENERAPAN DATA MINING PADA TRANSAKSI PENJUALAN MENGGUNAKAN ALGORITMA APRIORI DI ALFAMART CENTRE PARK - Zega, Martinus; Fauzi, Rahmat (Computer Science and Industrial Engineering, 2023)
Along with the development of the economy from year to year, the retail industry is one of several industries that is experiencing quite good development, one of which is PT Sumber Alfaria Trijaya Tbk. or commonly known as Alfamart. Marketing activities at Alfamart that focus on buying and selling food and non-food goods with a large enough number of transactions in total daily sales, a company needs analytical tools to provide useful information for the company. Because Alfamart is a large-scale retail company, there are several problems that are often encountered daily, namely determining the layout of goods that are less strategic and easily noticed by customers, not knowing which products are most often purchased simultaneously by consumers and several types of goods in an overstock warehouse. Therefore, research was carried out with the implementation of data mining on sales at Alfamart using the Apriori algorithm and testing using the Rapidminer software to produce the highest association rules. The results of this study are the discovery of 10 association rules with a minimum support of 40% and 70% confidence which are expected to be recommendations for business actors to improve sales strategy.